2019
DOI: 10.1037/cdp0000223
|View full text |Cite
|
Sign up to set email alerts
|

Making my family proud: The unique contribution of familism pride to the psychological adjustment of Latinx emerging adults.

Abstract: , S. (2019). Making my family proud: The unique contribution of familism pride to the psychological adjustment of Latinx emerging adults. Cultural Diversity and Ethnic Minority Psychology 25(2), 188-198.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Strong familism can shield against damage from the negative aspects of risk (Deane et al, 2020). Aspects of familism related to interconnection and pride serve as a protective factor for positive psychosocial outcomes (Stein et al, 2019). Familism may also moderate the relation between stress and internalizing and externalizing behavior under some conditions (Umaña-Taylor et al, 2011), although it has also been shown to relate to higher levels of internalizing behaviors (Kuhlberg et al, 2010), and to increase risk of distress among adolescents under some conditions (Hernández et al, 2010).…”
Section: Psychosocial Adjustment: Individual Level Of Analysismentioning
confidence: 99%
“…Strong familism can shield against damage from the negative aspects of risk (Deane et al, 2020). Aspects of familism related to interconnection and pride serve as a protective factor for positive psychosocial outcomes (Stein et al, 2019). Familism may also moderate the relation between stress and internalizing and externalizing behavior under some conditions (Umaña-Taylor et al, 2011), although it has also been shown to relate to higher levels of internalizing behaviors (Kuhlberg et al, 2010), and to increase risk of distress among adolescents under some conditions (Hernández et al, 2010).…”
Section: Psychosocial Adjustment: Individual Level Of Analysismentioning
confidence: 99%
“…For example, Owens et al (2018) in their study of undergraduates who experienced stressful events, found both anxiety and avoidance attachment styles to be associated with depression symptom severity. In a separate study on the impact of culturally specific attachment bonds on depression, Stein et al (2019) found that familism pride was correlated with lower depression levels for Latinx college students.…”
Section: Depressionmentioning
confidence: 94%
“…Attachment bonds consist of a strong desire to maintain close proximity to one's primary caregiver and generate distress at the termination of the relationship (Ainsworth, 1989). In Latinx culture, familismo describes the development and maintenance of these bonds with family and others, and includes the valuing of obligation, support, and respect toward familial ties (Stein et al, 2019;Vesely et al, 2014).…”
Section: Early Maladaptive Schemas (Ems) and Attachment Stylementioning
confidence: 99%
See 1 more Smart Citation
“…18 Hence, community resilience (ie, bringing communities together for a common cause) 72 may help facilitate a sense of belongingness in one's community; thereby promoting positive adjustment through the upregulation of positive emotions (eg, pride). 73,74 Therefore, future research should consider the interplay of individual and environmental resilience factors to help identify mechanisms influencing positive outcomes across demographic groups.…”
Section: Strengths and Limitationsmentioning
confidence: 99%